Prolegomena to a history of Islamicate Manichaeism - Reeves, John C. (London : Equinox Publishing Ltd, 2011)
Prolegomena to a History of Islamicate Manichaeism provides an annotated anthology of primary sources highlighting Manichaeism, a dualist religion emerging in Mesopotamia in the third century and which spread rapidly throughout the Roman and Sasanian empires until it was violently suppressed by both polities. It nevertheless continued to flourish - largely clandestinely - in the Near East, Central Asia, and China until it finally disappeared at the beginning of the seventeenth century. This book translates and assesses the importance of a number of Arabic, Persian, Syriac, and even Hebrew lang.
Cover; Contents; Preface; Abbreviations and Conventions; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chronological Arrangement of Authorities; Bibliography; Indices; Index of Citations of Primary Sources; Index of Ancient and Medieval Authors, Tradents, and Personages; Index of Scriptural and Parascriptural Characters; Index of Manichaeans and of Individuals Suspected or Accused of Zandaqa; Index of Modern Authors
Description based upon print version of record.
Keywords: Manichaeism -- Apologetic works -- Early works to 1800.; Manichaeism -- History -- Sources; Manichaeism -- History; Manichaeism -- Relations; RELIGION / Gnosticism; Manichaeism -- History; Manichaeism -- Relations; Electronic books